Analisis Perbandingan Pengendalian Manajemen: Studi Kasus: Pelanggaran Karyawan Terkait Keuangan Perusahaan - Jessica Violita Hadi; Putri Ayu Evitasari; Hwihanus Hwihanus (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The Internal Control System is a form of company that uses it for the purpose of controlling and classifying several functions in order to achieve company goals and run according to plan effectively and efficiently. In Indonesia, the internal control system adheres to the principles of the Committee of Sponsoring Organization of the Treadway Commission (COSO). The creation of this principle is a form of resistance to fraud which is currently rampant. In this analysis, researchers used descriptive qualitative method techniques. This research data was taken from primary data and interview techniques, observation and literature study. The results of this research analysis show that there are external and internal pressures and supervision is less effective so it is proven to have a big influence on the conditions that occur in financial reports. Meanwhile, the financial target variables, change of auditor, change of leadership were proven to have no positive effect on the condition of the financial statements. The variables pressure, opportunity, rationalization and ability simultaneously have a significant effect on the condition of the company's financial statements. In this research analysis, the main objective is to carry out an analysis of Fraud actions and describe the forms of Fraud prevention actions carried out in the company in accordance with the COSO principles that will be applied in the company.